TSAT is a better predictor than ferritin of hemoglobin response to Epoetin alfa in US dialysis patients. Issue 1 (22nd August 2013) - Gaweda, Adam E.; Bhat, Premila; Maglinte, Gregory A.; Chang, Chun‐Lan; Hill, Jerrold; Park, Grace S.; Ashfaq, Akhtar; Gitlin, Matthew
Abstract Clinical guidelines recommend concurrent treatment of anemia in end‐stage renal disease with erythropoiesis‐stimulating agents (ESAs) and iron. However, there are mixed data about optimal iron supplementation. To help address this gap, the relationship between iron markers and hemoglobin (Hb) response to ESA (Epoetin alfa) dose was examined. Electronic medical records of 1902 US chronic hemodialysis patients were analyzed over a 12‐month period between June 2009 and June 2010. The analysis included patients who had at least one Hb value during each 4‐week interval for four consecutive intervals (k − 2, k − 1, k, and k + 1; k is the index interval), received at least one ESA dose during intervals k − 1 or k, had at least one transferrin saturation (TSAT) value at interval k, and at least one ferritin value during intervals k − 2, k − 1, or k. Effect modification by TSAT and ferritin on Hb response was evaluated using the generalized estimating equations approach. Patients had a mean (standard deviation) age of 62 (15) years; 41% were Caucasian, 34% African American, 65% had hypertension, and 39% diabetes. Transferrin saturation, but not ferritin, had a statistically significant (P < 0.05) modifying effect on Hb response. Maximum Hb response was achieved when TSAT was 34%, with minimal incremental effect beyond these levels. Of the two standard clinical iron markers, TSAT should be used as the primary marker of the modifying effect of iron on Hb response to ESA. Long‐term safety of iron use to improve Hb response to ESA warrants further study.